The high Arctic in extreme winters: vortex, temperature, and MLS and ACE-FTS trace gas evolution - Manney, G. L.; Daffer, W. H.; Strawbridge, K. B.; Walker, K. A.; Boone, C. D.; Bernath, P. F.; Kerzenmacher, T.; Schwartz, M. J.; Strong, K.; Sica, R. J.; Krüger, K.; Pumphrey, H. C.; et al. (Atmospheric Chemistry and Physics, 2008)
The first three Arctic winters of the ACE mission represented two extremes of winter variability: Stratospheric sudden warmings (SSWs) in 2004 and 2006 were among the strongest, most prolonged on record; 2005 was a record cold winter. Canadian Arctic Atmospheric Chemistry Experiment (ACE) Validation Campaigns were conducted at Eureka (80° N, 86° W) during each of these winters. New satellite measurements from ACE-Fourier Transform Spectrometer (ACE-FTS), Sounding of the Atmosphere using Broadband Emission Radiometry (SABER), and Aura Microwave Limb Sounder (MLS), along with meteorological analyses and Eureka lidar temperatures, are used to detail the meteorology in these winters, to demonstrate its influence on transport, and to provide a context for interpretation of ACE-FTS and validation campaign observations. During the 2004 and 2006 SSWs, the vortex broke down throughout the stratosphere, reformed quickly in the upper stratosphere, and remained weak in the middle and lower stratosphere. The stratopause reformed at very high altitude, near 75 km. ACE measurements covered both vortex and extra-vortex conditions in each winter, except in late-February through mid-March 2004 and 2006, when the strong, pole-centered vortex that reformed after the SSWs resulted in ACE sampling only inside the vortex in the middle through upper stratosphere. The 2004 and 2006 Eureka campaigns were during the recovery from the SSWs, with the redeveloping vortex over Eureka. 2005 was the coldest winter on record in the lower stratosphere, but with an early final warming in mid-March. The vortex was over Eureka at the start of the 2005 campaign, but moved away as it broke up. Disparate temperature profile structure and vortex evolution resulted in much lower (higher) temperatures in the upper (lower) stratosphere in 2004 and 2006 than in 2005. Satellite temperatures agree well with lidar data up to 50–60 km, and ACE-FTS, MLS and SABER show good agreement in high-latitude temperatures throughout the winters. Consistent with a strong, cold upper stratospheric vortex and enhanced radiative cooling after the SSWs, MLS and ACE-FTS trace gas measurements show strongly enhanced descent in the upper stratospheric vortex in late January through March 2006 compared to that in 2005.